Theoretical Analysis of Electromagnetic Torque of the Slotted-type Magnetic Couplers - Yang Chaojun; Sun Xianyou; Ma Chao; Gu Lixiang; Liang Xinghai; Wang Jian (Jixie chuandong)
A magnetic equivalent circuit method that can consider differences and interactions of each branch magnetic circuit was proposed for the solution of the output torque of slotted-type equivalent couplers. Due to the slotted form of the conductor rotor, the branches composed of the air gap, conductor, and tooth slot corresponding to the permanent magnet in the magnetic circuit are not the same. The specific form of each branch is related to the relative position of the inner and outer rotors. Since the conductor rotor adopts the slotted-type form, the branch magnetic circuits consist of air gap, conductor and cogging under the permanent magnet are different. The specific form of the magnetic circuit is related to the relative position of the inner and outer rotors. The magnetic equivalent circuit method was used to consider the influence of different branch magnetic circuits on the electromagnetic torque and it was solved as a whole taking into account the interaction between the branches, so as to improve the calculation accuracy of the output torque of slotted-type equivalent couplers. Finally, the proposed method was used to predict the output torque of the magnetic couplers under different slip rates, pole-arc/pole-pitch ratios and slotting ratios, and the theoretical verification was carried out by 3D finite element analysis and experiments. It is verified that the proposed method can meet the accuracy requirements of engineering applications.